Design of cationic nanostructured heterolipid matrices for ocular delivery of methazolamide - Youshia J (Dove Medical Press, 2012)
John Youshia, Amany O Kamel, Abdelhameed El Shamy, Samar MansourPharmaceutics and Industrial Pharmacy Department, Faculty of Pharmacy, Ain Shams University, Cairo, EgyptAbstract: Solid lipid nanoparticles (SLNs) formulated from one type of lipid (homolipid) suffer from low drug encapsulation and drug bursting due to crystallization of the lipid into the more ordered β modification, which leads to decreased drug entrapment and faster drug release. This study assessed the feasibility of using nanostructured lipid matrices (NLMs) for ocular delivery of methazolamide-(MZA) adopting heterolipids composed of novel mixtures of Compritol® and cetostearyl alcohol (CSA), and stabilized by Tween 80®. The systems were prepared using the modified high shear homogenization followed by ultrasonication method, which avoids the use of organic solvents. A 32 full factorial design was constructed to study the influence of two independent variables, namely the ratio of CSA:Compritol and the concentration of Tween 80, each in three levels. The dependent variables were the entrapment efficiency percentages (EE%), mean particle size (PS), polydispersity index (PDI), and zeta potential (ZP). In vivo intraocular pressure (IOP) lowering activity for the selected formulae was compared to that of MZA solution. The results showed that increasing the ratio of CSA to Compritol increased the EE% and PS, while increasing the concentration of Tween 80, decreased PS with no significant effect on EE%. The ZP values of all formulae were positive, and greater than 30 mV. The best formula, composed of 4% CSA, 2% Compritol, 0.15% stearylamine, and 2% Tween 80, with EE% of 25.62%, PS of 207.1 nm, PDI of 0.243, and ZP of 41.50 mV, showed in vitro sustained release properties for 8 hours and lowered the intraocular pressure by 8.3 mmHg within 3 hours, with this drop in pressure lasting for 12 hours.Keywords: nanostructured lipid matrices, heterolipids, factorial design, cetostearyl alcohol, methazolamide, ocular delivery